Geological conditions for lateral sealing of active faults and relevant research methods - Guang Fu; Mingwang Zhan (Natural Gas Industry B, 2017)
Many researchers worked a lot on geologic conditions for lateral sealing of faults, but none of their studies took the effect of internal structures of fault zones on the lateral sealing capacity of faults. Therefore, the lateral sealing of active faults has rarely been discussed. In this paper, based on the analysis of the composition and structure characteristics of fault fillings, the geological conditions for lateral sealing of active faults and relevant research method were discussed in reference to the lateral sealing mechanisms of inactive fault rocks. It is shown that, in order to satisfy geologically the lateral sealing of active faults, the faults should be antithetic and the faulted strata should be mainly composed of mudstone, so that the displacement pressure of fault fillings is higher than or equal to that of reservoir rocks in oil and gas migration block. Then, a research method for the lateral sealing of active faults was established by comparing the displacement pressure of fillings in the fault with that of reservoir rocks in oil and gas migration block. This method was applied to three antithetic faults (F1, F2 and F3) in No. 1 structure of the Nanpu Sag, Bohai Bay Basin. As revealed, the fillings of these three active faults were mostly argillaceous at the stage of natural gas accumulation (the late stage of Neogene Minghuazhen Fm sedimentation), and their displacement pressures were higher than that of reservoir rocks in the first member of Paleogene Dongying Fm (F1 and F3) and the Neogene Guantao Fm (F2). Accordingly, they are laterally sealed for natural gas, which is conducive to the accumulation and preservation of natural gas. Industrial gas flow has been produced from the first member of Paleogene Dongying Fm in Well Np101, the Guantao Fm in Well Np1-2 and the first member of Paleogene Dongying Fm in Well Np1, which is in agreement with the analysis result. It is verified that this method is feasible for investigating the lateral sealing of active faults.